Somatostatin - Hidayatullah, Rian; Budiawan, Hendra; Darmawan, Budi; Affandi, Erwin (Faculty of Medicine Universitas Mataram, 2021)
Somatostatin, also known as growth hormone-inhibiting factor (GIF) or somatotropin release-inhibiting factor (SRIF), is a peptide hormone that regulates the endocrine system and affects neurotransmission and cell proliferation. Somatostatin can be regarded as secretory pan-inhibitory,because it can inhibit secretion of almost all endocrine and exocrine glands. Somatostatin has 2 active forms (somatostatin-14 and 28), but the short half-life of the hormone was one of the reasons why the native hormone was not feasible for routine clinical practice. Somatostatin analog was synthesized for the first time in 1980-1982 and proved to be more resistant to degradation and more potent than native hormone. There are five somatostatin receptors (SSTR1-5). The genes encoding human SSTR1-5 are located in chromosome 14q13, 17q24, 22q13.1, 20p11.2 and 16p13.3. SSTR expression pattern and complex signaling make somatostatin be such an extraordinary neurotransmitter and hormone. The potent inhibitory action of SSTR on cellular processes such as secretion, proliferation, and apoptosis is the reason for somatostatin to be the target for therapy development. Radiopharmaceuticals used for therapy consist of three parts: somatostatin analog, chelator, and radionuclide (alpha or beta-emitting). Combinations of different peptides, chelators, and radionuclides have been tested in vitro and/or in vivo for their use in peptide receptor radionuclide therapy (PRRT). These compounds are able to irradiate tumors and their metastases via the internalization through a specific receptor subtype which is generally overexpressed on the cell membrane.